Correlation between carotid artery ultrasound parameters and lacunar infarction - Peipei Yang; Ying Hui; Shuohua Chen; Xinyu Zhao; Wei Huang; Xiaoshuai Li; Shouling Wu; Yuntao Wu; Ling Yang; Jing Chen; Zhenchang Wang; Xian-Quan Shi (BMC Medical Imaging)
Abstract Objective This study aims to investigate the correlation between the imaging characteristics of lacunar infarction (LI) and carotid artery ultrasound parameters within a community-based population. Methods A total of 630 participants were included to undergo brain MRI and carotid ultrasound examinations, with their demographic and clinical characteristics systematically documented. Ultrasound imaging was used to quantify the structural, hemodynamic, and stiffness parameters of the common carotid artery (CCA) and internal carotid artery (ICA). Additionally, the associations between these parameters and the imaging features of LI were comprehensively analyzed. Result The mean age of the participants was about 55.21 ± 10.98 years, and the prevalence of LI was 13.02% (82/630). As shown by correlation analysis, all carotid artery ultrasound parameters exhibited significant correlations with LI except for ICA-PSV. Internal diameter of CCA and ICA, plaque in CCA and ICA, resistance index (RI) of CCA and ICA, pulsatility indexes (PI) of CCA and ICA, systolic/diastolic(S/D) of CCA and ICA, and carotid-femoral pulse wave velocity (cf-PWV) were positively associated with LI; peak systolic velocities (PSV) of CCA, end-diastolic velocities (EDV) of CCA and ICA, average velocity (AVG) of CCA and ICA were negatively associated with LI. Multivariate regression analysis showed that CCA-internal diameter (95%CI, 1.04–1.93; p = 0.025), CCA-plaque (bilateral) (95%CI, 1.06–4.37; p = 0.034), and cf-PWV (95%CI, 1.01–1.15; p = 0.017) were independent factors of presence of LI. Conclusion Arterial plaque burden and stiffness-related parameters assessed through carotid artery ultrasound, such as CCA-internal diameter, CCA-plaque, and cf-PWV, show predictive value for the risk of LI.